Fractal-like kinetic modelling for sorption of diclofenac onto graphene oxide/polypyrrole composite: Mechanism analysis and response surface methodology for optimization (2023)
Graphene oxide/polypyrrole (GO/PPy) composite material was prepared to explore its utility in the removal of diclofenac from aqueous system. The characterization was achieved using Fourier transform infrared spectroscopy, X-ray powder diffraction analysis, thermogravimetry-differential thermal analyses, scanning electron microscopy coupled with energy dispersive X-ray analysis and transmission electron microscopy analysis. Response surface methodology was exploited to optimize the process variables for the sorption of diclofenac onto GO/PPy. Three variables such as contact time, adsorbent dose and initial concentration of diclofenac were selected for optimization to achieve maximum removal of diclofenac. All experiments were conducted at pH 5. The contact time, adsorbent dose and initial concentration of diclofenac were examined in the ranges of 03–37 min, 13–147 mg/25 mL and 10–110 mg/L, respectively. The optimum values obtained were: contact time: 20 min; GO/PPy dose: 80 mg/25 mL and initial diclofenac concentration: 60 mg/L. The maximum sorption capacity and percent removal of diclofenac were found to be 29.50 mg/g and 98.50 %, respectively. The measured data (at equilibrium) were investigated using different isotherm models and best described by Freundlich model (R2 = 0.9943–0.9952, χ2 = 0.0062–0.0077, APE = 1.45–1.61). The experimental kinetic data were analyzed with the help of fractal-like kinetic models. The kinetic data are best fitted by fractal-like mixed 1,2 order (R2 = 0.9830–0.9886, χ2 = 0.0014–0.0036, APE = 0.6780–1.1059). Adsorption mechanism has been discussed based on kinetic, FTIR and molecular docking studies which indicated the participation of π-π interactions and hydrogen bonding on energetically heterogeneous surface. The adsorption/desorption test demonstrated that GO/PPy had excellent reusability performance up to 15 cycles.